In search of a ‘good number’: knowledge controversy and population estimates in the endgame of hepatitis C elimination - Rhodes, Tim; Lancaster, Kari; Adams, Sophie (BMJ global health, 2024)
We explore the contentious life of a metric used to assess a country’s progress in relation to global disease elimination targets. Our topic is hepatitis C elimination, and our context is Australia. A fundamental metric in the calculation of progress toward hepatitis C elimination targets, as set by the WHO, is the population prevalence of people living with hepatitis C. In Australia, this modelled estimate has generated some controversy, largely through its repeated downsizing as an effect of calculus. The 2015 baseline population estimate in Australia, from which measures of current elimination progress are assessed, has reduced, over time, by around 30%. Informed by a social study of science approach, we used qualitative interviews with 32 experts to explore the knowledge controversy. The controversy is narrated through the core concerns of ‘scale’ and ‘care’, with narratives aligning differently to imaginaries of ‘science’ and ‘community’. We trace how constitutions of ‘estimate’ and ‘number’ circulate in relation to ‘population’ and ‘people’, and as affective values. We show how enactments of estimates and numbers materialise hepatitis elimination in different ways, with policy implications. The event of the knowledge controversy opens up the social and political life of enumerations—for science and community—inviting deliberation on how to make ‘good numbers’ in the race to eliminate hepatitis C.